Mareva injunction as a preventive relief: the Malaysian experience - Ali, Zuraidah (International Islamic University Malaysia, 2009)
Mareva injunction generally results from a successful application to freeze the assets of the defendant prior to trial. In Malaysia, the application for the Mareva injunction did not get a good start, on the ground that the Malaysian court had no jurisdiction to grant such relief. The legal remedy under the Debtors Act 1957, by way of attachment of property before judgement was also an obstacle to the introduction of the Mareva injunction. It was only in 1984, in the case of Zainal Abidin v. Century Hotel Sdn Bhd, that such an application was granted when Raja Azlan CJ held that Mareva injunction shoud be available in Malaysia to fulfill modern commercial need. This paper examines the development of the Mareva injunction and its implementation in Malaysia. The research methodology which is adopted in this paper is mainly case law analysis. There will also be a brief appraisal of the application of Mareva injunction from the Shariah perspective.